Books and written culture of the Islamic world studies presented to Claude Gilliot on the occasion of his 75th birthday : Islamicae litterae scripta Claudio Gilliot septuagesimum quintum diem natalem celebranti dicata - Rippin, Andrew, 1950-; Tottoli, Roberto.; Gilliot, Claude. (Islamic History and Civilization, 2015)
In celebration of the many contributions of Claude Gilliot to Islamic studies, an international group of twenty-one friends and colleagues join together to explore books and written culture in the Muslim world. Divided into three sections - authors, genres and traditions - the essays explore themes that have been of central interest and concern to Gilliot himself including the Qurʾān, tafsīr, ḥadīth, poetry, and mysticism. Gilliot's detailed and extensive work on many authors and texts, literary genres, and specific case-studies on many Muslim traditions renders this volume an apt tribute to him as well as offering Islamic studies' scholars valuable research insights on these subjects. The authors of these English, French and German essays are all renowned scholars from Europe and North America, each of whom have benefitted substantially from Gilliot's work and collegiality. With contributions by: Mohammad Ali Amir-Moezzi, Mehdi Azaiez, Anne-Sylvie Boisliveau, Abdallah Cheikh-Moussa, Jean-Louis Déclais, Denis Gril, Manfred Kropp, Pierre Larcher, Michael Lecker, Jane Dammen McAuliffe, Harald Motzki, Tilman Nagel, Angelika Neuwirth, Emilio Platti, Jan van Reeth, Andrew Rippin, Uri Rubin, Walid Saleh, Roberto Tottoli, Reinhard Weipert, Francesco Zappa